Managing sub-gingival fracture by multi-disciplinary approach: Endodontics-forced orthodontic extrusion and prosthetic rehabilitation - Rakesh Mittal; Sumit Gupta; Anchal Singla; Anshu Gupta (Wolters Kluwer Medknow Publications, 2013)
Traumatized anterior teeth with sub-gingival crown fractures are a challenge to treat. The management of sub-gingival fractures includes exposing the cervical margin followed by appropriate coronal restoration. The treatment modalities, which involve exposing the cervical margin, are surgical crown lengthening and orthodontic extrusion. This paper reports a case of fractured maxillary anterior tooth at the sub-gingival level that was managed by forced orthodontic extrusion after endodontic treatment followed by esthetic rehabilitation, a much forgotten technique not utilized routinely yet conservative and cost-effective.